2001
DOI: 10.1074/jbc.m004389200
|View full text |Cite
|
Sign up to set email alerts
|

Novel G Proteins, Rag C and Rag D, Interact with GTP-binding Proteins, Rag A and Rag B

Abstract: Rag A/Gtr1p are G proteins and are known to be involved in the RCC1-Ran pathway. We employed the two-hybrid method using Rag A as the bait to identify proteins binding to Rag A, and we isolated two novel human G proteins, Rag C and Rag D. Rag C demonstrates homology with Rag D (81.1% identity) and with Gtr2p of Saccharomyces cerevisiae (46.1% identity), and it belongs to the Rag A subfamily of the Ras family. Rag C and Rag D contain conserved GTP-binding motifs (PM-1, -2, and -3) in their N-terminal regions. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
213
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(221 citation statements)
references
References 55 publications
(47 reference statements)
2
213
0
2
Order By: Relevance
“…1C) as a result of a large conformational transition, which is described below in detail. This finding is consistent with a previous observation that Mg 2ϩ is not required for GDP binding to RagC (4). Biochemical studies suggested that the absence of Mg 2ϩ ion can increase the rate of GDP dissociation up to 1000-fold (11,12).…”
Section: Overall Structure Of the Gtr1psupporting
confidence: 82%
See 2 more Smart Citations
“…1C) as a result of a large conformational transition, which is described below in detail. This finding is consistent with a previous observation that Mg 2ϩ is not required for GDP binding to RagC (4). Biochemical studies suggested that the absence of Mg 2ϩ ion can increase the rate of GDP dissociation up to 1000-fold (11,12).…”
Section: Overall Structure Of the Gtr1psupporting
confidence: 82%
“…Rag GTPases exist as heterodimers containing a Gtr1p-like Rag GTPase (either RagA or RagB) and a Gtr2p-like Rag GTPase (either RagC or RagD) (4). The function of the heterodimeric complex relies on which guanine nucleotide is bound to each of the Rag GTPases.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…EGO1/MEH1, EGO3/NIR1/ SLM4, GTR1, or GTR2) or a decrease in TORC1 signalling , see also above) provides further circumstantial evidence for an intriguing model in which EGOC relays vacuolar nutrient signals to TORC1. Although the function of EGO1/MEH1 and EGO3/NIR1/SLM4 is not yet clear, GTR1 and GTR2 are small GTPases and the yeast orthologues of the mammalian RagA, -B, -C and -D proteins (Sekiguchi et al, 2001). Notably, RagC is upregulated in metastatic mammalian cells and suggested to be involved in malignant progression (Nakaji et al, 1999).…”
Section: Regulation Of Torc1 By Nutrientsmentioning
confidence: 99%
“…Rag GTPases are evolutionarily conserved throughout eukaryotes. Higher eukaryotes have four members of Rag GTPases: RagA, RagB, RagC and RagD (Sekiguchi et al, 2001). Rag GTPases exist in heterodimeric complexes consisting of RagA or RagB and RagC or RagD (Dubouloz et al, 2005;Hirose et al, 1998;Kim et al, 2008).…”
Section: Introductionmentioning
confidence: 99%